Kajian Kriminologi Terhadap Penyalahgunaan Minuman Beralkohol Tradisional Bagi Perilaku Remaja - Yuni Kartika Latumahina; Margie Gladies Sopacua; Steven Makaruku (Faculty of Law, Universitas Pattimura, 2023)
Introduction: The habit of the people to drink traditional liquor in Ambon City is usually used more for traditional events and has become a tradition that still exists today, this is done with the aim of strengthening fraternal relations and maintaining unity, but it is different from the current situation where drinking more widely known by teenagers than among parents.Purposes of the Research: Aims to study and explain what factors cause the abuse of Alcoholic Drinks and the impact on the abuse of Alcoholic Drinks for adolescents in Galunggung, Ambon City. The method used in this paper is juridical sociology which in other words is field research. This type of research is descriptive analysis. Types and sources of data consist of primary data and secondary data. Data collection techniques were carried out by means of interviews, observations and literature studies. Analyzed qualitatively. Methods of the Research: In this legal research, the author uses sociological juridical research. Sociological juridical research is a field research. This type of sociological juridical research uses primary data, with primary data obtained directly from the source so that it is still in the form of raw data.Results of the Research: The results of the study that cause adolescents to abuse alcoholic beverages are caused by several factors such as adolescent individual factors, family factors, lack of religious education, economic factors and environmental factors.